Similarities and differences in residents’ perception of housing adequacy and residential satisfaction - Ibem, E.O.; Adeboye, A.B.; Alagbe, O.A. (Penerbit UKM, 2015)
Housing adequacy and residential satisfaction are two concepts used to evaluate the extent to which housing schemes meet residents’ needs and expectations. However, the differences and similarities in the way residents understand these concepts have not been properly articulated in the research literature. This study therefore investigated the differences and similarities in residents’ perception of housing adequacy and residential satisfaction with a view to identifying the dimensions of housing adequacy and residential satisfaction evaluation; and the factors that influenced this. The data were derived from a questionnaire survey of 517 residents in public housing in Ogun State, Nigeria; and analyzed using descriptive statistical, factor and categorical regression analyses. The result shows that whereas the residents evaluated housing adequacy based on four key dimensions: ambient condition of interior spaces; security, utilities and neighbourhood facilities; social infrastructure and sizes of main activity areas, residential satisfaction was evaluated based on three dimensions: the physical, social and economic environment of the housing estates; size, type, location, appearance; privacy and security of the residences. Residential satisfaction, tenure and income emerged as the three strongest predictors of housing adequacy, while housing adequacy, employment status and sex of the respondents were the three strongest predictors of residential satisfaction. Age of the respondents was found to be the only predictor of both housing adequacy and residential satisfaction. The key implication of the study is that, in housing research, each of these two concepts can serve as a surrogate for each other. It also implies that to improve the living conditions of residents of public housing, housing policy makers and developers should pay sufficient attention to the needs of all categories of residents by making sure that the housing preferences of workers in the different sectors and age groups are properly incorporated into future housing projects.